2015
DOI: 10.12720/joaat.2.2.129-133
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of 3-Hydroxystigmastan- 5(6)-en (β-Sitosterol) Compound from Salacca Edulis Reinw Variety Bongkok in MCF-7 and T47D Cell Line

Abstract: Discovery of two compounds in ethylacetate extract of snake fruits (Salacca edulis Reinw) variety Bongkok were pyrolle-2,4-dicarboxylic acid-methyl ester and 3-hydroxystigmastan-5(6)-en (β-sitosterol) compounds. In a previous study, two new compounds were observed an antioxidant activity by 2,2-diphenylpicrylhydrazyl (DPPH) free radical scavenging activity. Pyrolle-2,4-dicarboxylic acid-methyl ester posses cytotoxic activity against MCF7 and T47D cell line. 3-hydroxystigmastan-5(6)-en (βsitosterol) from snake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…We reported that the ethyl acetate fraction of S. edulis contained a number of phytochemical constituents such as glycosides, flavonoids, and tannins (Table 1). Afrianti et al discovered that the ethyl acetate fraction of S. edulis contained a number of phytochemical compounds such as 3-hydroxystigmastan-5(6)-en and pyrolle-2,4-dicarboxylic acid, methyl ester [24], whereas another phytochemical screening study also reported that S. edulis contained flavonoids and tannins [24,25]. The positive results for glycosides detected in this current research are expected to be associated with the high sugar content in S. edulis.…”
Section: Phytochemical Screeningsupporting
confidence: 55%
“…We reported that the ethyl acetate fraction of S. edulis contained a number of phytochemical constituents such as glycosides, flavonoids, and tannins (Table 1). Afrianti et al discovered that the ethyl acetate fraction of S. edulis contained a number of phytochemical compounds such as 3-hydroxystigmastan-5(6)-en and pyrolle-2,4-dicarboxylic acid, methyl ester [24], whereas another phytochemical screening study also reported that S. edulis contained flavonoids and tannins [24,25]. The positive results for glycosides detected in this current research are expected to be associated with the high sugar content in S. edulis.…”
Section: Phytochemical Screeningsupporting
confidence: 55%
“…Salak fruit is traditionally used by Malaysians to treat diabetes. Several studies reported that the salak fruit possesses anticancer, antihyperuricemic, antioxidant, antidiabetic, and proliferative activities [ 3 , 4 , 5 , 6 , 7 ]. Gorinstein and associates performed in vitro and in vivo studies where they compared the antioxidant properties of rare exotic Thai fruits with conventional fruits, and found that there was a significant reduction of plasma lipid profile, as well as maintained plasma antioxidant activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salacca is a species of the palm tree (Arecaceae) native to Java and Sumatra in Indonesia. It contains dietary fiber and carbohydrates that are good for the body (Chareoansiri et al, 2009). The taxonomy of salacca plants is (Cronquist, 1981) (Naharudin, 2019 ).…”
Section: Origin and Botanical Classificationmentioning
confidence: 99%
“…The proximate analysis of 100 g of zalacca resulted in sucrose (7.6%), fructose (5.9%), fructose (3.9%), total sugar (17.4%), soluble dietary fiber (0.3%), insoluble dietary fiber (1.4%), water (80%), calories (77 kcal), protein (0.7%), ash (0.6%), and fat (0.1%). The contents of vitamins and minerals in 1 kg of the salacca fruit are ascorbic acid (400 mg), carotene (5 mg), thiamine (20 mg), niacin (240 mg), riboflavin (0.8 mg) and folate (6 mg), phosphorus (1.161 mg), potassium (11.339 mg), calcium (220 mg), magnesium (607 mg), sodium (231 mg), iron (12.0 mg), manganese (10.4 mg), copper (3.36 mg), zinc (10.4 mg), boron (5.07 mg), and sulfur (5.07 mg) (Chew et al, 2012;Gorinstein et al, 2009;Janick and Paull, 2008).…”
Section: Nutritional Contentsmentioning
confidence: 99%
See 1 more Smart Citation